Electoral Malpractices and the Challenges of Democratic Sustainability in Nigeria, 1979-1999 - Aworawo, Friday (Àgídìgbo: ABUAD Journal of the Humanities, 2013)
Electoral malpractices have posed serious challenges to democratic sustainability in Nigerian since independence. The process of electoral malpractices often started from the registration of voters through the nomination of candidates, the conduct of elections as well as to the point of announcing losers and winners. The results of conducting elections not devoid of rigging have culminated into protest and counter protest as well as the fall of different regimes in the political history of Nigeria. The consequences of these have been cautious efforts by successive administration to engender an electoral framework that would ensure free, fair and credible elections. This work examines the nature and patterns of electoral process in Nigeria from 1979 elections, which marked the beginning of the second republic, and 1999 elections, which commenced the start of the fourth republic in Nigerian political history. And concludes that in order to avoid a repeat of history there should be serious reforms of all the political parties, the governmental electoral umpire saddled with the responsibilities of conducting elections and more importantly the attitudinal change of Nigerians toward conducting elections that would be acceptable to everyone and the international communities